Optimalisasi Penggunaan Buku Teks dalam Upaya Meningkatkan Prestasi Belajar di SMP - Kulsum, Dewi Umi (Manajemen Pendidikan, 2015)
This research  aim to description  about  usage  of textbook  in the effort increasing achievement of matter learning Travelling at educative participant of class VIII B State of Junior  High School  two Cawas  Region  Klaten  even semester  of school  year 2014/2015. Subject   and   research   data   source   is  22  students.   Data   collecting   method   applies observation, documentation,  and test. Data analysis applies critical analysis and comparability.  Indicator success of using minimal limit criteria 75 and complete target of100%. Research procedure applies cycle. Result of inferential research and solution: From continuation  data  of  enclosure  5,  yard,  data  obtained  from  finite  precycle  of  cycle  II, obtained  progress  of achievement  of student  learning  in study  of English  with  matter Travelling,  at precycle average of 76,1 and cycle I average of 78,7 and cycle II average of89,8 Of data is, seems to explain that happened increase of average of value from precycleto cycle I 2,6 numbers  (3,4%),  from cycle I to cycle II happened  increase  11,2 numbers (10,8%), from pasiklus to cycle II happened increase 12,1 numbers (16,8%). Highest value of phase  precycle  82 and cycle  I 84 and cycle  II 96. Seems  to explain  that from  phase precycle  to cycle I happened  increase  equal to 2 number (2,4%),  from cycle I to cycle II happened  increase 12 numbers  (14,2%),  and from precycle to cycle II happened  increase13,8 numbers (18,1%). Low value of phase precycle is obtained by 68 and cycle I 74 andcycle II 84. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 6 number (8,8%), from cycle I to cycle II happened increase 10 numbers (13,5%), and from precycle to cycle II happened increase 16 numbers (24%). Complete percentage learnt starts from precycle is obtained equal to 64% and cycle I is obtained equal to 90% and cycle II equal to 100%. Seems to explain that from phase precycle to cycle I happened increase equal to 26%, from cycle I to cycle II happened increase equal to 10%, and from precycle  to cycle  II happened  increase  equal  to 36%.  Thereby,  achievement  of student learning  in  study  of  English  with  matter  Travelling  from  finite  precycle  of  cycle  II happened increase significant.